Reduced striatal brain volumes in non-medicated adult ADHD patients with comorbid cocaine dependence - van Wingen, Guido A.; van den Brink, Wim; Veltman, Dick J.; Schmaal, Lianne; Dom, Geert; Booij, Jan; Crunelle, Cleo L. (Drug and alcohol dependence, 2013)
Adult attention deficit/hyperactivity disorder (ADHD) is highly comorbid with other psychiatric disorders, including substance use disorders (SUD). Patients with ADHD and SUD comorbidity respond less well to pharmacological treatment (e.g., methylphenidate), have more severe ADHD symptoms, and are generally more impulsive than ADHD patients without SUD. However, little is known about structural brain abnormalities that may differentiate ADHD patients with and without comorbid SUD. We compared regional grey matter volumes of 10 non-medicated male ADHD patients with comorbid cocaine dependence, 14 non-medicated male ADHD patients without cocaine dependence and 15 healthy control participants matched for age and premorbid intellectual functioning, using voxel-based morphometry (VBM) using both a whole-brain analysis and a priori ROI analysis based on the existing ADHD VBM literature. In a whole brain analysis, ADHD patients with and without cocaine dependence showed smaller volumes in the right putamen and cerebellum compared to healthy controls. In addition, ADHD patients without cocaine dependence showed larger volumes in the midbrain and in the precentral gyrus compared to healthy control participants and larger volumes in the occipital cortex compared to ADHD patients with comorbid cocaine dependence. A direct comparison using the a priori defined ROI approach showed that ADHD patients with cocaine dependence had smaller putamen volumes than ADHD patients without cocaine dependence. ADHD patients with cocaine dependence show more profound grey matter volume reductions in the striatum compared to ADHD patients without cocaine dependence. Possible implications for treatment are discussed.